STIMULASI KOGNITIF LANSIA MELALUI MOKA GAMES DI WILAYAH SIMOKERTO KOTA SURABAYA - Putri, Linta Meyla; Kristiani, Rina Budi; Istifada, Rizkiyani; Wijaya, Hermanto (PPM STIKES Adi Husada, 2024)
Introduction & Aims: According to WHO, there are 65.6 million elderly people throughout the world who experience impaired cognitive function. The impact of cognitive disorders in the elderly causes a shift in the role of the elderly in social interactions in society and within the family, followed by a decrease in physical and mental activity, impaired social function, and a decrease in quality of life. East Java is in second place with the highest dementia rate with a dementia prevalence of 10.40% and increasing with each passing year. Based on preliminary data in the RW 07 area, Kapasan, Simokerto District, the risk of cognitive impairment in the elderly is in fourth place with a percentage of 20%. So it is important to intervene regarding the risk of cognitive impairment in the elderly. The aim of this activity was to stimulate the cognitive abilities of the elderly through MOKA Games. Method of Activity: Community service activities were carried out in the RW.07 area, Kapasan, Simokerto District, Surabaya City, in February 2024. Implementation of this activity included opening, filling out the pre-test, explaining the material using leaflets, MOKA (Cognitive Monitoring of the Elderly) demonstration. Games, discussions, and post-test completion. MOKA Games is a game innovation based on the MMSE instrument, equipped with a guidebook containing a game monitoring table, each player has a monitoring table containing the score for each question. Result: There was an increase in audience knowledge as shown by an increase in the percentage of knowledge from pre-test to post-test, apart from that respondents were able to carry out a MOKA Games simulation with the direction of elderly cadres. Discussion: Cognitive stimulation activities for the elderly through MOKA Games received a positive response and good enthusiasm from the audience, with MOKA Games we can find out the condition of cognitive abilities and stimulate the elderly.